2008
DOI: 10.1111/j.1746-1049.2008.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Networks and Exports: Results From Indonesian Panel Data

Abstract: Most firms and plants in developing countries produce only for the domestic market and few are able to export. One plausible hypothesis is that foreign networks decrease export costs and that plants with large amounts of such networks will be relatively likely to start exporting. We focus on two types of foreign networks: foreign ownership and imports of intermediate products. Our results suggest that plants in Indonesian manufacturing with any foreign ownership are substantially more likely to start exporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
3
21
0
1
Order By: Relevance
“…A high portion of foreign capital encouraged the firm to export in the industrial estate. These results support Sjöholm and Takii (2008) who found that foreign capital firms are more likely to export than domestically funded firms in Indonesia. The main reason of why foreign capital might encourage export is global production network.…”
Section: The Role Of Industrial Estate Characteristics On Firm's Exposupporting
confidence: 82%
See 1 more Smart Citation
“…A high portion of foreign capital encouraged the firm to export in the industrial estate. These results support Sjöholm and Takii (2008) who found that foreign capital firms are more likely to export than domestically funded firms in Indonesia. The main reason of why foreign capital might encourage export is global production network.…”
Section: The Role Of Industrial Estate Characteristics On Firm's Exposupporting
confidence: 82%
“…The higher the foreign share, the higher the export opportunities. Sjöholm and Takii (2008) found that in Indonesia firms that use foreign capital are more likely to export than domestically funded firms. However, the influence of a firm's age on its export decision is still inconclusive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sjöholm (2003b) 1996 Exports Foreign firms are better able to start exporting than local firms. Sjöholm and Takii (2008) 1990-2000 Exports Foreign firms are better able to start exporting than local firms. Sjöholm (2004a) 1996 Wages per employee Foreign firms pay higher wages than local firms.…”
Section: Productivitymentioning
confidence: 99%
“…Some of them focus on the impact of foreign intermediate inputs on the probability of exporting (Sjöholm and Takii, 2008;Aristei et al, 2013;Lo Turco and Maggioni, 2013;Giovannetti et al, 2013;Meinen, 2015) and others on export volume and export scope (Bas and StraussKahn, 2014;Bertrand, 2011;Feng et al, 2012;Navas et al, 2013). 4 To the best of our knowledge, this is the first study that is focused on the impact of being an importer of intermediate inputs on the probability that a firm will cease exporting, which is our main contribution to this strand of literature.…”
Section: _________________________mentioning
confidence: 99%